FRONT COVER - Wiguna, Putu Perdana Kusuma (International Journal of Biosciences and Biotechnology; Vol 8 No 2 (2021): International Journal of Bioscience and Biotechnology, 2021)
Front Cover IJBB Vol. 8 No 2 September 2021